Essential oil of piper betle linn, and its chemistry - Wan Mohd. Nuzul Hakimi Wan Salleh, 1987-; Farediah Ahmad, supervisor; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2009